Evaluating 3D printing to solve the sample-to-device interface for LRS and POC diagnostics: example of an interlock meter-mix device for metering and lysing clinical urine samples. Issue 10 (28th April 2016) - Jue, Erik; Schoepp, Nathan G.; Witters, Daan; Ismagilov, Rustem F.
Abstract : Rapid prototyping of a meter-mix device to accurately meter, lyse, and transfer urine samples for LRS and POC diagnostics. Abstract : This paper evaluates the potential of 3D printing, a semi-automated additive prototyping technology, as a means to design and prototype a sample-to-device interface, amenable to diagnostics in limited-resource settings, where speed, accuracy and user-friendly design are critical components. As a test case, we built and validated an interlock meter-mix device for accurately metering and lysing human urine samples for use in downstream nucleic acid amplification. Two plungers and a multivalve generated and controlled fluid flow through the device and demonstrate the utility of 3D printing to create leak-free seals. Device operation consists of three simple steps that must be performed sequentially, eliminating manual pipetting and vortexing to provide rapid (5 to 10 s) and accurate metering and mixing. Bretherton's prediction was applied, using the bond number to guide a design that prevents potentially biohazardous samples from leaking from the device. We employed multi-material 3D printing technology, which allows composites with rigid and elastomeric properties to be printed as a single part. To validate the meter-mix device with a clinically relevant sample, we used urine spiked with inactivated Chlamydia trachomatis and Neisseria gonorrhoeae . A downstream nucleic acid amplification by quantitative PCR (qPCR) confirmed there was no statistically significant difference between samples metered and mixed using the standard protocol and those prepared with the meter-mix device, showing the 3D-printed device could accurately meter, mix and dispense a human urine sample without loss of nucleic acids. Although there are some limitations to 3D printing capabilities ( e.g. dimension limitations related to support material used in the printing process), the advantages of customizability, modularity and rapid prototyping illustrate the utility of 3D printing for developing sample-to-device interfaces for diagnostics.